Pengembangan Media Pembelajaran Saintifik berbasis Multimedia melalui Model Discovery Learning - Mohamad Fatih (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2018)
Based on the observations conducted in August-September in elementary school on learning conducted by elementary school teachers in Blitar there is learning, media is still using conventional media in the form of images. Solutions to improve the learning conditions that have been found above by developing learning media in accordance with the curriculum, characteristics of student development and the characteristics of learning materials. This research method using R & D. There are four phases in the process of making instructional media, (1) basic competence analysis and learning indicators, (2) character analysis and learning materials, (3) analysis of student characteristics, and (4) making of scientific learning media with Power Pont application. Media feasibility test results by media and material experts are rated